Real-world effectiveness of COVID-19 vaccines and anti-SARS-CoV-2 monoclonal antibodies against postacute sequelae of SARS-CoV-2: analysis of a COVID-19 observational registry for a diverse US metropolitan population - Tannous, Jonika; Pan, Alan P; Potter, Thomas; Bako, Abdulaziz T; Dlouhy, Katharine; Drews, Ashley; Sostman, Henry Dirk; Vahidy, Farhaan S (BMJ open, 2023)
ObjectivesWe evaluated the effectiveness of COVID-19 vaccines and monoclonal antibodies (mAbs) against postacute sequelae of SARS-CoV-2 infection (PASC).Design and settingA retrospective cohort study using a COVID-19 specific, electronic medical record-based surveillance and outcomes registry from an eight-hospital tertiary hospital system in the Houston metropolitan area. Analyses were replicated across a global research network database.ParticipantsWe identified adult (≥18) patients with PASC. PASC was defined as experiencing constitutional (palpitations, malaise/fatigue, headache) or systemic (sleep disorder, shortness of breath, mood/anxiety disorders, cough and cognitive impairment) symptoms beyond the 28-day postinfection period.Statistical analysisWe fit multivariable logistic regression models and report estimated likelihood of PASC associated with vaccination or mAb treatment as adjusted ORs with 95% CIs.ResultsPrimary analyses included 53 239 subjects (54.9% female), of whom 5929, 11.1% (95% CI 10.9% to 11.4%), experienced PASC. Both vaccinated breakthrough cases (vs unvaccinated) and mAb-treated patients (vs untreated) had lower likelihoods for developing PASC, aOR (95% CI): 0.58 (0.52–0.66), and 0.77 (0.69–0.86), respectively. Vaccination was associated with decreased odds of developing all constitutional and systemic symptoms except for taste and smell changes. For all symptoms, vaccination was associated with lower likelihood of experiencing PASC compared with mAb treatment. Replication analysis found identical frequency of PASC (11.2%, 95% CI 11.1 to 11.3) and similar protective effects against PASC for the COVID-19 vaccine: 0.25 (0.21–0.30) and mAb treatment: 0.62 (0.59–0.66).ConclusionAlthough both COVID-19 vaccines and mAbs decreased the likelihood of PASC, vaccination remains the most effective tool for the prevention of long-term consequences of COVID-19.